2017
DOI: 10.1007/s12325-017-0530-y
|View full text |Cite
|
Sign up to set email alerts
|

Stevens-Johnson Syndrome and Toxic Epidermal Necrolysis: A Concise Review with a Comprehensive Summary of Therapeutic Interventions Emphasizing Supportive Measures

Abstract: IntroductionStevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) are two of the most severe dermatologic conditions occurring in the inpatient setting. There is a lack of consensus regarding appropriate management of SJS and TEN.PurposeThe scientific literature pertaining to SJS and TEN (subsequently referred to as SJS/TEN) is summarized and assessed. In addition, an interventional approach for the clinician is provided.MethodsPubMed was searched with the key words: corticosteroids, cyclosporine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
152
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(168 citation statements)
references
References 59 publications
0
152
0
5
Order By: Relevance
“…While the exact mechanism of SJS and TEN remains unclear, perforin, granzyme B, and granulysin are considered "key mediators" in its pathogenesis (Schneider & Cohen, 2017). Studies have demonstrated that by inhibiting these mediators and reducing their expression, cytotoxicity is diminished (Chung, Wang, & Dao, 2016;Nassif et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the exact mechanism of SJS and TEN remains unclear, perforin, granzyme B, and granulysin are considered "key mediators" in its pathogenesis (Schneider & Cohen, 2017). Studies have demonstrated that by inhibiting these mediators and reducing their expression, cytotoxicity is diminished (Chung, Wang, & Dao, 2016;Nassif et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated that by inhibiting these mediators and reducing their expression, cytotoxicity is diminished (Chung, Wang, & Dao, 2016;Nassif et al, 2002). Nuclear factor-κB is then inhibited, thus halting apoptosis and stopping the disease process (Schneider & Cohen, 2017;Stern & Divito, 2017). Cyclosporine inhibits the early phases of activation of CD4+ and CD8+ T cells, which subsequently inhibits the secretion of granulysin, granzyme, and perforin.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have found that levels of TNF‐alpha are also upregulated in the pathogenesis of SJS/TEN, inducing keratinocyte apoptosis (Paradisi et al, ). TNF‐alpha inhibitors such as infliximab and particularly etanercept have been reported as treatment options for SJS/TEN and are thought to prevent disease progression and increase survival (Paradisi et al, ; Schneider & Cohen, ). With TNF‐alpha playing a role in the pathogenesis of both TSS and SJS/TEN, etanercept, a TNF‐alpha inhibitor, may be a reasonable treatment option for cases where prompt treatment is desired but diagnosis is uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…Mortality can be even higher in elder patients and patients in whom the area of skin necrolysis is large [25]. Although systemic interventions may change the clinical course of this disease, local supportive therapy increases the survival rate and accelerates wound healing (Figure 4) [28].…”
Section: Use Of Amnion In the Treatment Of Shallow Skin Losses And Inmentioning
confidence: 99%